1983
DOI: 10.3109/00365528309181643
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Transit Time in Constipated and Non-Constipated Geriatric Patients

Abstract: Intestinal transit was measured by following a radioisotope capsule through the gut. The transit in 16 elderly patients with chronic constipation was compared with that in 16 patients of the same age and with 10 healthy younger people without constipation. Although the constipated patients generally had a slower total transit time through the gut, some old and young people without constipation also showed a slow total transit. Constipated patients had a significantly slower transit only through the rectosigmoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 8 publications
1
20
0
1
Order By: Relevance
“…However, there is no evidence of altered bowel habits towards constipation with advancing age per se [4], While in rats a marked prolongation of large intestine transit has been observed with in creasing age [26] we could not demonstrate any difference in whole-gut transit -mainly reflecting large-intestine transit -of a mixed solid-liquid meal including an unresorbable carbohydrate (lactulose) between young and old subjects with normal bowel habits. This observation corresponds to the findings of Melkerson et al [17], who did not find any age-related changes of intestinal transit of a radioisotope capsule in young and aged sub jects unaffected by constipation.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…However, there is no evidence of altered bowel habits towards constipation with advancing age per se [4], While in rats a marked prolongation of large intestine transit has been observed with in creasing age [26] we could not demonstrate any difference in whole-gut transit -mainly reflecting large-intestine transit -of a mixed solid-liquid meal including an unresorbable carbohydrate (lactulose) between young and old subjects with normal bowel habits. This observation corresponds to the findings of Melkerson et al [17], who did not find any age-related changes of intestinal transit of a radioisotope capsule in young and aged sub jects unaffected by constipation.…”
Section: Discussionsupporting
confidence: 73%
“…Conflicting data of previous studies suggest that a prolonged gastric emptying time might occur with increasing age, but only a few studies applied adequate methods like radionuclide-labelled meals rather than unphysiological ingestions such as barium sulphate [7,14,19,25]. Data concerning age-related changes of small-intestine motil ity are sparse and suggest that there might be a slight reduction of small-bowel motor ac tivity in elderly subjects [1], Such motility changes and the known age-related decrease in small-intestine absorptive capacity could be related to alterations of small-intestine transit, but studies that systematically ad dress this issue are not available [13], Infor mation on whole-gut transit, predominantly reflecting colon transit, is likewise rare in the elderly: although constipation is a wellknown problem in geriatric patients, there is no unequivocal evidence that colonic transit increases with age [17],The purpose of this study therefore was to assess the influence of age on the gastro …”
mentioning
confidence: 99%
“…It is still controversial whether the CTT is prolonged in the elderly as reported by Merkel et al [19] or does not change with ageing as reported by Evans et al [18], Eastwood [20], and Melkersson et al [21].…”
Section: Discussionmentioning
confidence: 80%
“…There appears to be a decrease in gastric emptying with age, but the magnitude of change is still controversial (review in 7, 8). While it is well known that constipation is a common problem in older people,4, 9, 10 the effect of age on colonic transit is unclear with both a slowing of, and no change in transit reported 11, 12…”
Section: Introductionmentioning
confidence: 99%